Modelling the influence of changing climate in present and future marine eutrophication impacts from spring barley production - Cosme, Nuno; Niero, Monia (Journal of cleaner production, 2017)
Nitrate concentration and runoff are site-specific and driven by climatic factors and crop management. As such, nitrate emissions may increase in the future due to climate change, affecting the marine eutrophication mechanism. In this context, and considering the case of spring barley production in Denmark, the paper has two objectives: (i) to estimate the present and future marine eutrophication impacts by combining a novel Life Cycle Impact Assessment (LCIA) modelling approach with a quantification of the effects of climate change on its parameterisation, and (ii) to discuss the implications of different normalisation references when comparing future Life Cycle Assessment (LCA) scenarios with current production systems. A parameterised characterisation model was developed to gauge the influence of future climatic-driven pressures on the marine eutrophication impact pathway. Spatial differentiation was added to the resulting ‘present’ and ‘future’ characterisation factors (CFs) and calculated for the Baltic and North Sea. The temporal variability of both midpoint normalised impact scores and damage scores reflect a 34% and 28% increase of the CFs in the North Sea and Baltic Sea, respectively. The temporal variability is mostly explained by CF variation and increasing future nitrogen flows. The marine eutrophication indicator scores at both midpoint and damage levels suggest that the differentiation of impacts to various receiving (and potentially perturbed) ecosystems is relevant. Damage scores are quantified with a factor 2.5 and 2.3 differentiation between the Baltic (higher) and North Seas (lower) for the present and future scenarios, respectively. The comparison of the normalisation methods, either based on total annual impacts (domestic inventory of background interventions), on ecological carrying capacity, or on the presently proposed method, point to the value of adding spatial differentiation to LCIA models. The inclusion of time variation and spatial differentiation in characterisation modelling of marine eutrophication and the identification of a paucity of adequate inventory data for future scenario analysis constitute the main outcomes of this study. Further research should aim at reducing the uncertainty of the parameterisation under future conditions and strengthening emissions projections. [Display omitted] •New marine eutrophication LCIA model applied to N emissions from barley production.•New CFs in PAF m3 yr kgN−1 cover a longer impact pathway than traditional midpoints.•Future climatic pressures were parameterised in marine eutrophication CFs.•Normalisation references on present and future scenarios are compared and discussed.•Time-dependent modelling, spatial differentiation and inventory data are key issues.